UN ESTUDIANTE CONFLICTIVO PARA MUCHOS, ES EN REALIDAD UN PERSONAJE CON MUCHO QUE DAR - LEIDY NATALY MATEUS AGUILERA (Universidad Distrital Francisco José de Caldas, 2010)
In this written presents a history that is repeat year to year for some educators that have as a goal to formation in aspects of type scientific and also as corresponding to social values; there is also a reflection that leads to evidence of bias, prejudice and the exclusion that is made, in some cases in the classroom, to students that present some difficulties, aspect that affects the formation of the student, the learning and evaluation. In the same way is presented as a suggestion the inclusion of values in the classroom regardless the area of knowledge, based on of a pedagogical model and psychological currents that allow establish academic links and reflections in the formation of human being.